The Role of Work Engagement in Determining Job Satisfaction: Examining Work-Family Conflict and Work Stress - Wiratama, Bayu; Wijaya, Angga Pandu; Dewi, Rara Hayu Noro Karti Sari (JDM (Jurnal Dinamika Manajemen), 2022)
This study is expected to examine the effect of work-family conflict and stress on job satisfaction with work engagement as a mediating variable. The study population was Bank Rakyat Indonesia Rembang Branch employees. The number of samples is 108 employees. Data collection has employed a questionnaire. The results showed that the mediating role of work engagement caused work-family conflict not significantly to affect job satisfaction, and work stress did not significantly affect job satisfaction. Work engagement had a positive and significant effect on job satisfaction. Work engagement proved to mediate work-family conflict on job satisfaction. Work engagement can mediate job stress on job satisfaction..